Utilizing Web Based Learning as 21st Century Learning Media for Vocational Education - Dika Tria Puspitasari, Ervina; Dwi Surjono, Herman; Dahar Minghat, Asnul (International Journal of Engineering and Technology, 2018)
This study examines the development of information technology that focuses on the use of web based learning as a learning medium in the world of vocational education. Web-based learning provides convenience for students in learning activities such as increasing productivity, flexible and interactive. The results obtained from several literature studies from journal articles, opinion papers, conceptual papers, etc. were analyzed for content related to the use of web based learning in the world of vocational education. The result of the literature review in this paper is that E-learning is a learning process that is poured through internet technology, with the principle of simple, personal, and fast need to be considered. Therefore, the principles and communication of learning need to be designed like conventional learning. The need for developing the right e-learning learning model according to needs. Web base learning is a learning model that requires technological tools, especially information technology such as computers and internet access. In practice, web base learning utilizes internet facilities as a medium for delivering information (material) learning such as websites, e-mail, mailing lists, and news groups. The planned use of web-based learning technology has proven to provide a significant contribution to the world of education, especially for vocational education that requires students to think critically. In implementing web based learning, there are several factors that need to be considered such as supporting facilities and infrastructure, users (students as users and teachers/lecturers/experts as material presenter), readiness of online materials and costs.Â  Â